P49 Time to SHINE – simulation to help in neonatal emergencies: a course to improve trainee confidence in neonatal emergency management. (November 2018) - Fullwood, Isobel; Holt, Ashley; Powell, Catherine; Baker, Nikki; Dhillon, Amrit; Hawkes, Alex; Cornes, Helen; Nash, Matthew
Abstract : Background: A scoping questionnaire for West Midlands Paediatrics trainees was carried out to assess the level of confidence in the management of various neonatal emergency scenarios and revealed that, for example, only 14% of trainees (ST1–7) felt 'quite confident' to manage PPHN. The questionnaire also assessed recent opportunities in/exposure to simulation based education in this field. Only 10% had received simulation based education atleast once a month and 81% felt there was not enough neonatal simulation based education. This needs assessment was the driving force to develop the first trainee SHINE course; Simulation to Help In Neonatal Emergencies. Summary of work: A one day course comprising of four neonatal emergency scenarios and two workshops was designed by a multi-disciplinary faculty based at Birmingham Women's Hospital. The course was free to attend for West Midlands trainees and was aimed at registrar or near registrar level trainees who wanted to gain confidence in the management of common neonatal emergencies. The learning objectives were both technical and non-technical. Results: The course was attended by six candidates ST3–4 level. 22% of the candidates had not been exposed to four of the scenarios on the course during their training so far. Before attending the course, 50% of the candidates had neutral or low confidence levels in the management of each scenario. After the course confidence levels improved to quite confident or very confident for 100% of the candidates. 100% of the candidates felt the scenarios were very relevant. All candidates felt the learning environment was safe and supportive and all candidates would recommend the course to a colleague. Learning points included both technical and non-technical skills and written feedback included 'It is so useful that I would make it compulsory'. Discussion: The need and demand for simulation based education in neonatal training in the West Midlands was identified and lead to the delivery of a pilot simulation based education course in response. The feedback received was overwhelmingly positive and it is felt this course can play a vital role in standardising exposure to neonatal emergency scenarios for West Midlands trainees and therefore improve confidence when faced with these scenarios during their training. We are running our second course in July 2018.